1981
DOI: 10.1002/food.19810250705
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in cereal grain. Part IV. Inactivation of ochratoxin A and other mycotoxins during ammoniation

Abstract: Addition of ammonia to final concentration 2% inactivates ochratoxin A, aflatoxin, citrinin, penicillic acid and partially zearalenon at temperature 20-50 degrees C. Detoxification of contaminated cereal grain (wheat, corn or barley) can be performed on a farm using ammoniation without special investment during 4 to 6 weeks. Ammoniation changes nutritional value of grain as feed in a small extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…Chelkowski and collaborators [79] reported that treatment of OTA-contaminated grain with ammonia reduced OTA concentrations to undetectable levels. Moreover, weight gains of chickens fed the OTA-contaminated grain were markedly decreased, whereas there was no reduction in weight gains when the chickens were fed the OTA-contaminated grain that had been ammoniated.…”
Section: Methods Of Prophylaxis and Various Preventive Measures Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelkowski and collaborators [79] reported that treatment of OTA-contaminated grain with ammonia reduced OTA concentrations to undetectable levels. Moreover, weight gains of chickens fed the OTA-contaminated grain were markedly decreased, whereas there was no reduction in weight gains when the chickens were fed the OTA-contaminated grain that had been ammoniated.…”
Section: Methods Of Prophylaxis and Various Preventive Measures Inmentioning
confidence: 99%
“…Moreover, weight gains of chickens fed the OTA-contaminated grain were markedly decreased, whereas there was no reduction in weight gains when the chickens were fed the OTA-contaminated grain that had been ammoniated. They concluded that ammoniation of grain not only detoxifies several mycotoxins, including OTA, but also inhibits mould growth [79]. Feeding studies have shown no toxic effects related to the ammoniation process, but there are some changes in the nutritional quality of the feed, such as a decrease in lysine and sulfur containing amino acids [80].…”
Section: Methods Of Prophylaxis and Various Preventive Measures Inmentioning
confidence: 99%
“…6 illustrates schematically the invasion of mycelium into kernels. Histochemical experiments supported conclusions of milling and pearling of wheat and barley kernels [2] as well as microbiological assays [4]. Ochratoxin A, a toxic metabolite of Aspergilli and Penicilliu in contaminated kernels, was found mainly in the same part of kernels and only small percentage in deeper layers and on surface [2].…”
Section: Resultsmentioning
confidence: 93%
“…The knowledge of the opening of the lactone ring in alkaline media explains, at posteriori, the "strange" results obtained by Chelkowski et al [25,26]. These authors, treated by ammoniation at ambient temperature a rat feed contaminated by OTA.…”
Section: Otamentioning
confidence: 86%